(untitled) (REMUNOM, 2023)
The search for the use of alternative materials is a measure that aims to contribute to sustainable development in the field of civil construction. As this sector consumes a large amount of natural resources and is responsible for releasing a large amount of carbon dioxide into the atmosphere when producing Portland cement, the use of waste from the manufacturing process of industries, which would be discarded, often inappropriate, contributes to greater protection of the environment. Thus, the main objective of this research is to verify the applicability of textile residues (sludge and wood ash) in cementitious matrices, through the physical and chemical characterization of these residues generated in an industry in the municipality of Estância/SE. The residues were submitted to characterization tests regarding their granulometric composition, specific mass, unitary mass, fineness index, liquidity limit, chemical composition (EDS for sludge and FRX for ash) and organic matter content. Finally, given the results obtained, it is believed that these residues can be used as a partial substitute for fine aggregate in the production of mortar or concrete without causing significant damage to the performance of these materials.